2013
DOI: 10.1021/la401702w
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Scaffold-Based Cardiac Tissue Engineering: Application of Coordinated Mechanical and Electrical Stimulations

Abstract: Recently, we have developed an optimal decellularization protocol to generate 3D porcine myocardial scaffolds, which preserved natural extracellular matrix structure, mechanical anisotropy, and vasculature templates, and also showed good cell recellularization and differentiation potential. In this study, a multi-stimulation bioreactor was built to provide coordinated mechanical and electrical stimulations for facilitating stem cell differentiation and cardiac construct development. The acellular myocardial sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 66 publications
3
87
1
4
Order By: Relevance
“…Though bioreactors that have both electrical and mechanical stimulation capabilities have been created previously, 14,25,26 to date, only one study has looked into the effects of combined electromechanical stimulation in cardiac engineered tissue. 27 In this study, Wang et al observed that electromechanical stimulation improved cardiac differentiation of mesenchymal stem cells and an increase in contractile proteins, such as a-actinin, myosin heavy chain, and connexin 43 (Cx43), as compared with those cultured statically. However, the electrical and mechanical stimulation were applied simultaneously, which is not physiologically relevant in the context of the heart, where mechanical stimulation represents the filling of the ventricles with blood and electrical stimulation of the ventricles to contract occurs just before the release of stretch.…”
Section: Introductionmentioning
confidence: 81%
“…Though bioreactors that have both electrical and mechanical stimulation capabilities have been created previously, 14,25,26 to date, only one study has looked into the effects of combined electromechanical stimulation in cardiac engineered tissue. 27 In this study, Wang et al observed that electromechanical stimulation improved cardiac differentiation of mesenchymal stem cells and an increase in contractile proteins, such as a-actinin, myosin heavy chain, and connexin 43 (Cx43), as compared with those cultured statically. However, the electrical and mechanical stimulation were applied simultaneously, which is not physiologically relevant in the context of the heart, where mechanical stimulation represents the filling of the ventricles with blood and electrical stimulation of the ventricles to contract occurs just before the release of stretch.…”
Section: Introductionmentioning
confidence: 81%
“…Electrical charges play an important role in stimulating either the proliferation or differentiation of various cell types [2][3][4]. Both in-vivo and in-vitro studies have demonstrated that electrical stimulation, either in AC, DC, or pulsed electromagnetic field can stimulate cell growth or bone regeneration [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, realization of this potential will be dependent on the ability of MSCs to recapitulate both anatomical and functional features of the different lung cell types. There is now considerable evidence that MSCs play a role in regeneration and repair (61,62,81,91,112,201) and in secretion of growth factors, immune modulators, and other factors that support the idea that MSCs may be better taken up in organ scaffolds (158,198,220), especially if scaffolds enhance their differentiation (86,219), presumably through cell-matrix interactions (64,161,174,232). Several studies have shown that MSCs can attach and proliferate in lung scaffolds (39,117,131,137).…”
Section: Recellularization In Lung Bioengineeringmentioning
confidence: 99%